From the high arctic to the equator: do soil metagenomes differ according to our expectations? - Kerfahi, Dorsaf; Tripathi, Binu M.; Dong, Ke; Kim, Mincheol; Kim, Hyoki; Ferry Slik, J. W.; Go, Rusea; Adams, Jonathan M. (Springer New York LLC, 2019)
Comparing the functional gene composition of soils at opposite extremes of environmental gradients may allow testing of hypotheses about community and ecosystem function. Here, we were interested in comparing how tropical microbial ecosystems differ from those of polar climates. We sampled several sites in the equatorial rainforest of Malaysia and Brunei, and the high Arctic of Svalbard, Canada, and Greenland, comparing the composition and the functional attributes of soil biota between the two extremes of latitude, using shotgun metagenomic Illumina HiSeq2000 sequencing. Based upon “classical” views of how tropical and higher latitude ecosystems differ, we made a series of predictions as to how various gene function categories would differ in relative abundance between tropical and polar environments. Results showed that in some respects our predictions were correct: the polar samples had higher relative abundance of dormancy related genes, and lower relative abundance of genes associated with respiration, and with metabolism of aromatic compounds. The network complexity of the Arctic was also lower than the tropics. However, in various other respects, the pattern was not as predicted; there were no differences in relative abundance of stress response genes or in genes associated with secondary metabolism. Conversely, CRISPR genes, phage-related genes, and virulence disease and defense genes, were unexpectedly more abundant in the Arctic, suggesting more intense biotic interaction. Also, eukaryote diversity and bacterial diversity were higher in the Arctic of Svalbard compared to tropical Brunei, which is consistent with what may expected from amplicon studies in terms of the higher pH of the Svalbard soil. Our results in some respects confirm expectations of how tropical versus polar nature may differ, and in other respects challenge them.